People’s Awareness on Coronavirus Disease (COVID-19) in the Context of its Transmission and Epidemiology — A Study - Satapathy, M.K. (SCHOOL SCIENCE, 2021)
A study on the awareness of Coronavirus Disease ( COVID-19) with 124 randomly selected people of Bhubaneswar reflected that 81 per cent of people believed it to be a killer disease. Very limited people had knowledge about symptoms of the disease. Less than 50 per cent understood about transmission of the virus, by mouth droplets. Though 42 per cent of people believed that masks could prevent disease transmission, a large number of people were found using masks improperly. A positive relation was found between education and awareness, but, age was found to have no impact on people’s awareness. In the absence of a vaccine or drug to control COVID-19, the possible means of preventing the disease and people’s awareness have been discussed.